2018
DOI: 10.1038/mi.2017.118
|View full text |Cite
|
Sign up to set email alerts
|

GPR43 mediates microbiota metabolite SCFA regulation of antimicrobial peptide expression in intestinal epithelial cells via activation of mTOR and STAT3

Abstract: The antimicrobial peptides (AMP) produced by intestinal epithelial cells (IEC) play crucial roles in the regulation of intestinal homeostasis by controlling microbiota. Gut microbiota has been shown to promote IEC expression of RegIIIγ and certain defensins. However, the mechanisms involved are still not completely understood. In this report, we found that IEC expression of RegIIIγ and β-defensins 1, 3, and 4 was lower in G protein-coupled receptor (GPR)43−/−mice compared to that of wild-type (WT) mice. Oral f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
259
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 354 publications
(290 citation statements)
references
References 51 publications
(69 reference statements)
10
259
0
4
Order By: Relevance
“…Bacteroides were shown to inhibit Salmonella Typhimurium through the production of the SCFA, propionate 12 . SCFAs also impact epithelial barrier function by affecting production of host molecules including antimicrobial peptides and epithelial mucins 13,14 . Disturbed microbiota and the loss of colonisation resistance are associated with several pathogen infections including Clostridioides difficile 8 , Enterohemorrhagic E. coli 15 , and Campylobacter jejuni 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Bacteroides were shown to inhibit Salmonella Typhimurium through the production of the SCFA, propionate 12 . SCFAs also impact epithelial barrier function by affecting production of host molecules including antimicrobial peptides and epithelial mucins 13,14 . Disturbed microbiota and the loss of colonisation resistance are associated with several pathogen infections including Clostridioides difficile 8 , Enterohemorrhagic E. coli 15 , and Campylobacter jejuni 16 .…”
Section: Introductionmentioning
confidence: 99%
“…; Zhao et al . ). There is also considerable evidence for direct and indirect effects of SCFAs on the brain (Dalile et al .…”
Section: Diet‐derived Microbial Metabolites In Health and Diseasementioning
confidence: 97%
“…Thus, SCFAs maintain intestinal homeostasis by regulating differentiation of T cells (Arpaia et al 2013;Furusawa et al 2013;Smith et al 2013;Sun et al 2018), promoting B-cell IgA production (Wu et al 2017) and protecting epithelial barrier integrity (Macia et al 2015;Zhao et al 2018). There is also considerable evidence for direct and indirect effects of SCFAs on the brain (Dalile et al 2019).…”
Section: Short-chain Fatty Acidsmentioning
confidence: 99%
“…Indeed, a recent study showed that optimal expression of AMPs requires IEC‐sensing of SCFAs via GPR43. Using Gpr43 −/− mice and enteroids, investigators observed that the AMPs RegIII γ and β ‐defensins 1, 3 and 4 were reduced in the absence of GPR43 or downstream mammalian target of rapamycin (mTOR) and signal transducer and activator of transcription 3 (STAT3) activation …”
Section: Microbiota–iec Crosstalkmentioning
confidence: 99%
“…Using Gpr43 À/ À mice and enteroids, investigators observed that the AMPs RegIIIc and b-defensins 1, 3 and 4 were reduced in the absence of GPR43 or downstream mammalian target of rapamycin (mTOR) and signal transducer and activator of transcription 3 (STAT3) activation. 33 Microbes also induce a number of non-barrier functions in IECs, including changes in metabolism and the biosynthesis of signalling molecules. For example, early during Citrobacter rodentium infection, IECs have been shown to exhibit changes in cholesterol and carbon metabolic pathways, suggesting that IEC metabolism is reprogrammed to meet increased cellular energetic demands during tissue repair.…”
Section: Microbial Regulation Of Iec Growth and Functionmentioning
confidence: 99%